2018
DOI: 10.1029/2018jd028820
|View full text |Cite
|
Sign up to set email alerts
|

Parameterized Vertical Concentration Profiles for Aerosols in the Marine Atmospheric Boundary Layer

Abstract: Information about sea spray aerosol particle transport and their vertical distribution in the marine atmospheric boundary layer (MABL) is important in marine meteorological forecasting and geobiochemical models. However, due to difficulties in field observations, values of aerosol concentration are often limited to point measurements, and obtaining the size‐resolved concentration profiles is quite challenging. Hence, numerical and analytical studies are vital in modeling the transport of aerosols in the atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 60 publications
(104 reference statements)
2
27
0
Order By: Relevance
“…The exponent p = 2 has been commonly used in the literature (Nissanka et al, 2018), while values between 2 and 3 agree with different observed profiles.…”
Section: Turbulent Mixingsupporting
confidence: 53%
See 1 more Smart Citation
“…The exponent p = 2 has been commonly used in the literature (Nissanka et al, 2018), while values between 2 and 3 agree with different observed profiles.…”
Section: Turbulent Mixingsupporting
confidence: 53%
“…The calculation for z i starts when the heat flux (w θ ) cpy first becomes positive in the morning, and continues one more hour after (w θ ) cpy becomes negative. The stability function φ(z/L) is given in equation 9 (Nissanka et al, 2018):…”
Section: Turbulent Mixingmentioning
confidence: 99%
“…D. Wei et al: FORest Canopy Atmosphere Transfer (FORCAsT) 2.0 The exponent p = 2 has been commonly used in the literature (Nissanka et al, 2018), while values between 2 and 3 agree with different observed profiles. The eddy diffusivity (K) parameterization based on mixing-length theory in FORCAsT 1.0 is described as follows, with greater detail presented in Forkel et al (2006) and Bryan et al (2012):…”
Section: Turbulent Mixingmentioning
confidence: 99%
“…It is apparent that the chemistry delineated by our experiments and analysis could rapidly process marine biogenic gas emissions whether at the ocean surface or on SSA. 49,7375…”
Section: Results and Discussionmentioning
confidence: 99%
“…Note that this estimate could be a lower limit if the reaction were also partially controlled by aqueous phase resistance in the surface of water. It is apparent that the chemistry delineated by our experiments and analysis could rapidly process marine biogenic gas emissions whether at the ocean surface or on SSA. , …”
Section: Results and Discussionmentioning
confidence: 99%